A Smart System to Ease Occurrence of Bedsores - Benjamin Kommey (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
The occurrence of bedsores in Ghanaian hospitals, elderly homes or care homes is especially high among patients or people who are incapacitated and cannot move or turn on their own, and who happen to remain in a particular posture for a very long time. Patients in coma, those operated on and for that matter in critical state, and patients confined to wheelchairs are primary examples. Constant pressure on some parts of the body leads to the occurrence of pressure sores or ulcers. This paper seeks to implement a Bedsore Easing System (BeSoSys) that integrate several embedded hardware components, a database and software to reduce the occurrence of bedsores. These embedded hardware components include the Bed Device Unit (BDU), the Pocket Device Unit (PDU), a pressure or weight sensor, a temperature sensor, and an inflation-deflation device. The BDU is fitted into the bed of the patient or on the surface of skin contact of the patient. The PDU is assigned to nurses or caretakers to serve as an alarm system for patient repositioning depending on situation. All activities in the Bedsore Easing System are logged into a database for future references. A bedridden patient exerts constant pressure on the bony protrusions of the body, and this causes bedsores. It was found out during the research that in Ghana, the nurses or caretakers used to turn and massage patients at some random time intervals as a way of preventing bedsores. This traditional way of turning and massaging patients is not only tedious but also ineffective. This paper seeks to provide easy, better, and effective solution to ease bedsores. The BeSoSys intends to prevent the occurrence of bedsores hence the alleviation of bedsore complications